Metal cluster models for heterogeneous catalysis: a matrix-isolation perspective; frontispiece - Hübner, Olaf; Himmel, Hans-Jörg (Chemistry - a European journal, 2018)
Within the concept of “molecular surface science”, the reactivity of clusters is studied to develop new mechanistic concepts for heterogeneous catalytic processes. The access to energetically low-lying excited states, which are often already populated at room temperature, is responsible for the high reactivity and selectivity of clusters. A systematic exploration of cluster reactivity comprises the detailed characterization of the clusters in their ground state and low-lying excited electronic states, paving the way for the exploration of their reactivity in dependence of their electronic state. The matrix isolation technique is ideally suited for this purpose, as it ensures that the clusters are in their electronic ground state from which they could be excited into other electronic states by irradiation. For more information, see the Review by H.-J. Himmel and O. Hübner on page 8941 ff.
Gesehen am 10.10.2019